Micronutrient supplementation and T cell-mediated immune responses in patients with tuberculosis in Tanzania. (July 2014) - KAWAI, K.; MEYDANI, S. N.; URASSA, W.; WU, D.; MUGUSI, F. M.; SAATHOFF, E.; BOSCH, R. J.; VILLAMOR, E.; SPIEGELMAN, D.; FAWZI, W. W.
SUMMARY Limited studies exist regarding whether incorporating micronutrient supplements during tuberculosis (TB) treatment may improve cell-mediated immune response. We examined the effect of micronutrient supplementation on lymphocyte proliferation response to mycobacteria or T-cell mitogens in a randomized trial conducted on 423 patients with pulmonary TB. Eligible participants were randomly assigned to receive a daily dose of micronutrients (vitamins A, B-complex, C, E, and selenium) or placebo at the time of initiation of TB treatment. We found no overall effect of micronutrient supplements on lymphocyte proliferative responses to phytohaemagglutinin or purified protein derivatives in HIV-negative and HIV-positive TB patients. Of HIV-negative TB patients, the micronutrient group tended to show higher proliferative responses to concanavalin A than the placebo group, although the clinical relevance of this finding is not readily notable. The role of nutritional intervention in this vulnerable population remains an important area of future research.